Household finances and trust are key determinants of benefits from small-scale fisheries co-management. (November 2022) - Kushardanto, Hari; Jakub, Raymond; Suherfian, Wahid; Subarno, Tarlan; Ansyori, Ahmad Isa; Sara, La; Alimina, Naslina; Fajriah; Kardini, La Ode; de la Rosa, Emilio; Yuliani, Ade; Medianti, Eva; et al.
Abstract: Socioeconomic conditions of small-scale fishing households often influence the benefits communities accrue from fisheries management interventions. Adjacent to seven newly established fisheries comanagement areas initiated in 2018, we examine the attributes of fishing households that influence perceived food, finance and job security, and compliance with fishing closures. We interviewed respondents from 1828 fishing households in 2019 and 2025 households in 2021 across the seven areas in Southeast Sulawesi, Indonesia. A key finding was that perceived food, financial and job security outcomes increased over the two-year period and were positively related to respondents knowledge of fisheries comanagement. Relationships between both household savings and loans and with household food security highlights the need for policy and institutional support for fishing households in times of need. Household income from fisheries and trust in community leaders was also related to higher reported compliance with fishing closures, suggesting that income security and community leadership are important drivers of adoption of comanagement resource harvest rules. In contrast, women who identified as fish processors reported that they did not comply with fishing closures, as likely they were not involved in management decision making. Moreover, the positive impact of respondent's trust in their community, on food, financial and job security, implies that strong community relationships can benefit well-being of coastal communities. Our findings highlight the need for programs that strengthen community institutions, improve household financial literacy, promote access to financial services and recognize gendered roles in fishing, as integral parts of community-based fisheries management. Highlights: Co-managed fisheries benefit household food, financial and job security. Household savings and income increase food, financial and job security. Household finances and trust in leadership drives support for fishing closures. Women fishers support household food and job security. Financing and gender policies are needed for sustainable fisheries management.